2019
DOI: 10.1007/s00508-019-01542-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between low back pain and various everyday performances

Abstract: SummaryLow back pain (LBP) is a widely prevalent chronic pain disorder associated with a high burden on individuals and society. In the subjective perception of patients with LBP, probably the most important health outcomes associated with LBP are those that effect everyday performance. Such outcomes include reduction in activities of daily living (ADL), in work ability (WA), and in sexual function. This narrative review aimed to (1) examine the association between LBP and the three mentioned outcomes of every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(51 citation statements)
references
References 58 publications
1
47
0
3
Order By: Relevance
“…Disability associated with chronic LBP is an intricate and multidimensional phenomenon [42] that further perpetuates chronicity of LBP [43,44]. Thus, disability resulting from LBP is associated with difficulty in performing almost all basic and instrumental activities of daily living [40,45].…”
Section: Discussionmentioning
confidence: 99%
“…Disability associated with chronic LBP is an intricate and multidimensional phenomenon [42] that further perpetuates chronicity of LBP [43,44]. Thus, disability resulting from LBP is associated with difficulty in performing almost all basic and instrumental activities of daily living [40,45].…”
Section: Discussionmentioning
confidence: 99%
“…A past comparative study between eperisone and baclofen also showed that both drugs have similar tolerability with no differences and minimum adverse effects. 13,19 In rheumatology practice, it is a common practice to combine analgesic (eg, NSAIDs) with a muscle relaxant (eg, thiocolchicoside or dantrolene), even using fixed-dose combinations to achieve a satisfactory reduction of both pain and muscle contracture. 20,21 There are several limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“… 10 11 CLBP has been shown to be strongly associated with a reduction in sexual activity. 12 13 Insomnia has also been frequently reported as a consequence of CLBP. 14 Some studies report an association of CLBP with earlier death, as they hypothesise that CLBP normally results in significant disability, which will cause activity limitation due to fear-avoidance behaviour.…”
Section: Introductionmentioning
confidence: 99%